Exenteration and Adjuvant Radiotherapy for Primary Carcinosarcoma of the Anterior Orbit: A Case Report. Issue 4 (July 2021) - Fernandez, Christian; Forrest, Paul; Sivalingam, Meera; Milman, Tatyana; Ramesh, Sathyadeepak; Shi, Wenyin
Abstract : Carcinosarcoma is a malignant mixed tumor composed of epithelial and mesenchymal components which arises in a variety of tissues, including, in rare cases, the orbit. A 75-year-old male with a history of basal cell carcinoma of the left medial canthus, previously treated with surgical resection and adjuvant radiation therapy, presented with a recurrent 3 cm nodule of the left medial canthus. He underwent surgical resection of the left superior and inferior eyelid with pathology revealing invasive squamous cell carcinoma of upper and lower eyelids with deep orbital tissue involvement and undifferentiated pleomorphic sarcoma involving the dermis and periosteum, consistent with carcinosarcoma. Orbital exenteration was subsequently performed. He successfully underwent adjuvant stereotactic body radiation therapy 30 Gy in 5 fractions with no significant side effects. Follow-up MRI revealed posttreatment changes without evidence of recurrent disease. Abstract : We report a case of a 75-year-old male with primary anterior orbital carcinosarcoma treated with exenteration and adjuvant radiotherapy due to the potential of recurrence and intracranial extension.